2023
DOI: 10.2147/ijgm.s394872
|View full text |Cite
|
Sign up to set email alerts
|

Events in CNS Tumor Pathology Post-2016 WHO CNS: cIMPACT-NOW Updates and Other Advancements: A Comprehensive Review Plus a Summary of the Salient Features of 2021 WHO CNS 5

Abstract: Introduction The 2016 World Health Organization Classification (WHO) of Tumors of the Central Nervous System (CNS) represented a major change. It recommended an “integrated diagnosis” comprising histologic and molecular information facilitating a more precise diagnosis of specific CNS tumors. Its goal was to provide greater diagnostic precision and reproducibility resulting in more clinical relevance and predictive value, ultimately leading to better patient care. Advances in molecular classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…According to the theory of clonal evolution, the accumulation of successive mutations within a cell leads to its extracellular proliferation, and these extracellular proliferations grow abnormally as a result of selection pressure from the microenvironment. Hypermutation is the mutation of specific genes in tumor cells, resulting in reduced sensitivity to drugs 58,59 . Immune evasion is the avoidance of tumor cells being recognized and attacked by the immune system, for example by suppressing the immune response.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…According to the theory of clonal evolution, the accumulation of successive mutations within a cell leads to its extracellular proliferation, and these extracellular proliferations grow abnormally as a result of selection pressure from the microenvironment. Hypermutation is the mutation of specific genes in tumor cells, resulting in reduced sensitivity to drugs 58,59 . Immune evasion is the avoidance of tumor cells being recognized and attacked by the immune system, for example by suppressing the immune response.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
“…Hypermutation is the mutation of specific genes in tumor cells, resulting in reduced sensitivity to drugs. 58 , 59 Immune evasion is the avoidance of tumor cells being recognized and attacked by the immune system, for example by suppressing the immune response. Gliomas reside in the brain and were previously thought to be immunologically privileged and immune surveillance spared, but recent studies have shown that the brain is an active regulatory point of immune surveillance.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%